Conceptualisation of sustainable consumer behaviour: converging the theory of planned behaviour and consumption cycle. Issue 1 (21st October 2021) - Sheoran, Monika; Kumar, Divesh
Abstract : Purpose: This article attempts to explore the theoretical model and structural dimensions of sustainable consumer behaviour to develop a "sustainable consumer behaviour scale" for sustainable electronic products. Further, this study has tried to elaborate sustainable consumer behaviour by considering the complete consumption cycle which includes purchase, usage and disposal of the sustainable electronic products. Design/methodology/approach: The theory of planned behaviour (TPB) has been employed to understand the multidimensional nature of sustainable consumer behaviour with the help of qualitative and quantitative methods. With the help of a pilot study followed by a main study, a sustainable consumer behaviour scale for sustainable electronic products has been tested and validated for its factor study, reliability, validity and model fit, etc. Moreover, the influence of demographic variables has also been examined with the help of multi-group analysis. Findings: This study highlights that the perceived control behaviour and subjective norms are the major factors that influence sustainable consumer behaviour. Moreover, the results also indicate that female consumers, mid income consumers, young consumers (age below 30) and consumers who have studied up to senior secondary level are more sustainable. Research limitations/implications: The results can be used by policymakers and managers to identify and target particular subjective norms and factors impacting perceived control behaviour along with a specific set of demographics to increase sustainability amongst consumers and businesses. The results of the current study can help in increasing the focus of the academic research towards sustainable consumer behaviour. It will also encourage firms to include sustainable electronic products in their product line. Originality/value: To the best of authors' knowledge, the current article is the first empirical study to develop a sustainable consumer behaviour scale by including all the different stages of the consumption cycle using TPB for sustainable electronic products. Although multiple efforts have been made by researchers to analyse sustainable consumer behaviour, there is a scarcity in literature in which research has been done to analyse sustainable consumer behaviour by considering the whole consumption cycle (purchase, usage and disposal).